A Review of the History of Attitudes Toward Drinking in Pregnancy. (July 2015) - Warren, Kenneth R.
<x xml:space="preserve">Abstract</x> Background It is now well accepted in pediatrics and obstetrics that prenatal alcohol is a teratogenic agent and the primary causative factor underlying fetal alcohol spectrum disorders (FASDs), although for the majority of the 20th century that knowledge was either unknown or ignored. At least 2 factors contributed to the delay in recognizing alcohol's role in teratogenicity: the rejection of earlier evidence pertaining to alcohol and pregnancy following the repeal of Prohibition in the United States, Canada, and several European countries; and misinterpretation of earlier research findings in a eugenic rather than toxicological context. The pervasive belief held well into the 1970s that there was no risk to either mother or fetus from prenatal alcohol posed a major challenge to changing physician and public attitudes on alcohol and pregnancy. This review provides insight on key events that occurred in changing physician and public understanding of the risks posed by prenatal alcohol use in pregnancy. Methods Historical review of events primarily in the U.S. federal government, found in referenced documents. Results The transition in physician and public understanding of the risks posed by prenatal alcohol use was aided by the existence of National Institute on Alcohol Abuse and Alcoholism (NIAAA) which was created in 1971. This government agency was able to support research on alcohol and pregnancy immediately following the 1973 published clinical reports calling attention to a proposed fetal alcohol syndrome (FAS). These early research studies provided the foundation for the first government health advisory on alcohol and pregnancy, issued by NIAAA in 1977. Subsequently, the U.S. Food and Drug Administration (FDA) used this new knowledge on FAS in their effort to add alcoholic beverages to the range of products with ingredient and consumer information labeling. The ensuing hearings and actions resulted in a new health advisory under the auspices of the Surgeon General, encouraging avoidance of alcohol consumption in pregnancy. In subsequent years, Congressional attention to the FAS issue resulted in the Alcoholic Beverage Labeling Law. Conclusions The pace at which understanding of the risks of prenatal alcohol moved forward from a total misunderstanding to acceptance was aided by both the efforts of the NIAAA in its support of research, and the FDA in its efforts to improve consumer information. Today, many women in the United States as well as other countries continue to ignore advisories on avoiding alcohol consumption in pregnancy, emphasizing the need for persistence in education on these health risks.